THE EFFORTS TO IMPROVE LEARNING OUTCOMES IN INDONESIAN LEARNING MATERIALS THROUGH JIGSAW LEARNING METHOD FOR VII GRADE STUDENTS VII DI UPTD SMP NEGERI 2 ULU PUNGKUT KABUPATEN MANDAILING NATAL IN 2021/2022 ACADEMIC YEAR - Mukhlis mukhlis (JURNAL LINER (Language Intelligence and Educational Research), 2022)
The type of this research is Classroom Action Research (CAR) using the Jigsaw Learning method which aims to determine the extent to which the use of this method can improve student learning outcomes in the Materials of Learning to Describe in Class VII UPTD. SMP Negeri 2 Ulu Pungkut, Mandailing Natal Regency. The subjects of this study were Class VII students with 19 students, 8 of whom were female and 11 were male. From the research carried out, it was found that the increase in students' Indonesian learning outcomes through the application of the Jigsaw Learning model in the Learning Materials to Describe. In the first cycle, the students' learning mastery percentage was obtained 57.9% and the score of class completeness was 71.4% with the lowest score 50 and the best score 70. In the second cycle, the students' learning completeness percentage was obtained by 100% and the class completeness score was 86.0%. with the lowest score of 70 and the best value of 90. This value has met the indicators of success. This means that there is an increase in students' Indonesian learning outcomes from cycle I to cycle II, for the percentage of mastery learning there is an increase of 42.1% and the score of class completeness is 14.5%. There is an increase in students' Indonesian learning activities through the Jigsaw learning model in Class VII UPTD. SMP Negeri 2 Ulu Pungkut Academic Year 2021/2022. This can be seen from the results of observations of student activities in the first cycle of 61.47%, while in the second cycle it is 72.95%. This means that there is an increase in student activity from cycle I to cycle II by 11.47%. There is an increase in teacher activity through the Jigsaw learning model in Class VII UPTD. SMP Negeri 2 Ulu Pungkut Academic Year 2021/2022. This can be seen from the results of observations of teacher activities in the first cycle of 76%, while in the second cycle it is 86%. This means that there is an increase in teacher performance from cycle I to cycle II by 10%.